My Brother Slaves : Friendship, Masculinity, and Resistance in the Antebellum South - Lussana, Sergio (Book collections on Project MUSE., 2016)
Trapped in a world of brutal physical punishment and back-breaking labour, Frederick Douglass mused that it was the friendships he shared with other enslaved men that carried him through his darkest days. In this study, Sergio A. Lussana offers an in-depth investigation of the social dynamics between enslaved men and examines how individuals living under the conditions of bondage negotiated masculine identities.